Evaluating the sensitivity and efficacy of fungicides with different modes of action against Neocosmospora solani and Fusarium species, causing agents of citrus dry root rot. (14th June 2022) - Ezrari, Said; Lazraq, Abderrahim; El Housni, Zakariae; Radouane, Nabil; Belabess, Zineb; Mokrini, Fouad; Tahiri, Abdessalem; Amiri, Said; Lahlali, Rachid
Abstract: Citrus dry root rot caused by members of Fusarium species is among the most devastating diseases that delimits citrus production worldwide. The present study aimed at evaluating the efficacy of fungicides against Fusarium solani (as Neocosmospora solani) and Fusarium spp. associated with citrus dry root rot in Morocco. Thirty-two isolates from different regions of Morocco were investigated for sensitivity to seven fungicides through the growth inhibition test. The half-maximal effective concentration (EC50 ) results revealed that the combination of trifloxystrobin + fluopyram and epoxiconazole were the best for the in vitro mycelial inhibition. Also, EC50 values for epoxiconazole, trifloxystrobin, fluopyram, trifloxystrobin + fluopyram, tetraconazole, thiophanate methyl, and penthiopyrade were ranging from 0.026 to 2.83 μg/ml, 2.47 to 82.35 μg/ml, 0.13 to 121.77 μg/ml, 0.37 to 14.41 μg/ml, 2.52 to 25.25 μg/ml and 2.02 to 44.88 μg/ml, respectively. The in vivo test suggested that the association between trifloxystrobin and fluopyram performed better in disease control than with other treatments' results. The evaluated fungicides showed high activity against Fusaria in vitro and demonstrated great efficacy for reducing the disease in the greenhouse trial. The study provides a basis for decision-making in the future development of new policies for preventing and controlling this disease.